Penanaman Pendidikan Karakter Disiplin dan Tanggung Jawab Melalui Metode Point Skorsing (studi kasus di SMK Negeri 8 Surakarta) - Setianto, Sandi (2016)
This research aimed to describe about investment, obstacles and solution in the investment of discipline character education and responsibility throught out suspention point method at SMK Negeri 8 Surakarta. This research data collected throught out the informans, places and events, as well as documents. Technique of collecting data using observation method, interview, documentation. Analysis of data using interactive model that have several steps of collecting data, reduction data, presentation data and conclusion. Investment of discipline character education and responsibility throught out suspention point method at SMK Negeri 8 Surakarta among student understanding the importance of time present, student habits to do the right rules, about the importance of wearing practice uniform, responsibility of keeping and outing the tools and materials, students should known about the job description, participate in school activities and have to express their opinions to solve the problems. The obstacles of investment discipline character education and responsibility throught out suspention point method at SMK Negeri 8 Surakarta among the student came late for the certain reasons, awarenessless about the importance of school rules, the students did not wearing practice uniform, lack of storage capacity the tools and materials, the students who undiscipline to finished the task regularly, the students not interest with school activities and passive to express their opinions. The conclusion for obstacles of investment of discipline character education and responsibility throught out suspention point method at SMK Negeri 8 Surakarta among suggest to students for more prepare in several things that need to do so their wont be late, giving the meaning the importance of school rules, give the punishment for students who did not wear practice uniform and the procurement of storage places of the tools and materials needed, give the instruction about the meaning of responsible, all of the student must have to attend the chool activities, and give the motivation to be brave to express the opinions.